The Current Trends and Gaps in Employee Innovation Literature (A Bibliometric Study) (West Science Business and Management, 2025)
Employee innovation has become an increasingly critical topic in organizational and management studies, as firms rely on the creative and proactive behaviors of their workforce to remain competitive in dynamic environments. Despite growing scholarly attention, the literature on employee innovation remains fragmented across constructs such as innovative work behavior, employee creativity, and employee-driven innovation. This study conducts a bibliometric analysis of publications indexed in Scopus between 2000 and 2025 to systematically map the intellectual structure, thematic evolution, and collaboration networks in this field. Using performance analysis and science mapping techniques with VOSviewer, the study identifies leadership, human resource management, and innovation performance as dominant research anchors, while recent trends highlight the emergence of inclusive leadership, sustainability, and psychological enablers such as self-efficacy. The collaboration networks reveal China and the United States as central hubs, with increasing contributions from Asian and European countries. The findings underscore both the maturity of core themes and the presence of underexplored areas, including employee-driven innovation and digital transformation contexts. This study contributes by clarifying research fragmentation, proposing the integration of dispersed strands into more holistic theoretical frameworks, and offering practical insights for organizations seeking to foster inclusive, sustainable, and innovation-driven work environments.